Variação e iconicidade: a representação morfossintática de uma hierarquia semântica (Revista de Estudos da Linguagem, 1998)
In portuguese if-clauses there occur three morphosyntactic alternativeforms – present indicative (PI), futur subjunctive (FS) and imperfectsubjunctive (IS). Traditional grammars correlate these to the threesemantic categories of realis, potentialis and irrealis. Actually, therealis appear only in PI and the irrealis in IS. However, sociolinguisticanalysis shows that the eventual potentialis often has a PI form; andthe habitual or generic potentialis, that are similar to the realis, mayappear in the FS. This paper focuses on the in/variability of theseforms. It identifies an iconically motivated epistemic hierarchy wherestatistical distribution codifies the probabilistic perception of thereality continuum.